Factors Related to Antibiotic Use Behavior Among Residents of Mueang District, Loei Province - Intaro, Wanassaporn; Songsilp, Sawitree (JOURNAL OF LOEI PROVINCIAL PUBLIC HEALTH OFFICE, 2025)
The objective of this study was to examine the antibiotic use patterns of the residents of Mueang District, Loei Province, and to investigate the factors associated with these patterns. The study employed a cross-sectional approach, collecting data from a sample of 438 individuals residing in 19 subdistricts within Mueang District, Loei Province. A questionnaire was used as the research tool. Descriptive statistics, including frequency, percentage, and mean values, were used to analyze personal characteristics such as gender, age, marital status, education level, and occupation. Chi-square statistics (χ2) were used to analyze factors related to antibiotic use behavior. The findings revealed that the majority of the sample was female (55.25%), with 42.47% aged between 45 and 59 years. Most participants obtained their antibiotics from public hospitals (28.91%), followed by private hospitals (24.90%) and hawkers (19.24%). The sample demonstrated a high level of knowledge about antibiotic use (50.23%) and exhibited appropriate antibiotic use behavior (62.56%). Age (χ2= 7.92; P = .04) and knowledge of antibiotic use (χ2= 47.42; P< .01) were found to be statistically significantly associated with antibiotic use behavior. The findings of this study suggest that appropriate antibiotic use behavior is influenced by both adequate knowledge and a suitable age. Therefore, providing regular and continuous education to the public about the proper use of antibiotics, especially among the working-age population and the elderly, can help promote more appropriate antibiotic use behavior.